2012
DOI: 10.1016/j.jpainsymman.2011.10.011
|View full text |Cite
|
Sign up to set email alerts
|

A Family’s Difficulties in Caring for a Cancer Patient at the End of Life at Home in Japan

Abstract: This study indicates that it is important for home care providers to introduce services to reduce care burden. In addition, a thorough explanation of the patient's symptoms and condition is necessary to reduce distress and anxiety for family caregivers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
24
0
5

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(31 citation statements)
references
References 21 publications
2
24
0
5
Order By: Relevance
“…Some categories of this concept, that is, patient-related stress, concern about future, stress, depression and grief, financial and physical problems, family challenges, sleep-related changes, psychological functional problems, loneliness and caregiving pressure are consistent with some research (4,7,8,(14)(15)(16)(17)(18). However, two sub-categories, namely, annoying and dysfunctional beliefs and resentment from the relatives are not seen in prior research.…”
Section: Discussionsupporting
confidence: 63%
“…Some categories of this concept, that is, patient-related stress, concern about future, stress, depression and grief, financial and physical problems, family challenges, sleep-related changes, psychological functional problems, loneliness and caregiving pressure are consistent with some research (4,7,8,(14)(15)(16)(17)(18). However, two sub-categories, namely, annoying and dysfunctional beliefs and resentment from the relatives are not seen in prior research.…”
Section: Discussionsupporting
confidence: 63%
“…2,[8][9] However, this opinion is not unanimous and may be related to the economy of each country, this can be seen in a study 23 which showed that the patients present better results when hospitalized, due to the government providing the treatment. Such results in the hospital environment may be related to the food shortage faced by patients when they are in their homes.…”
Section: ] At Home Privileging Those Related To Health Promotion Tmentioning
confidence: 99%
“…We justify the term "counter" because we understand that, as health professionals, we are considered state agents 6-7 who perform bio political interventions that guarantee the lives of people. Instead of saying that it is "better at home", as the studies say, [2][3][8][9] this study of genealogical inspiration placed the question of genesis and continuities under suspension, not definitively refusing them, but shaking the stillness from which we accept them, in addition to showing that they are not self-justifiable but that they are the effect of a construction whose rules must be known and the justifications controlled. 10 In view of this, we pretended with this study to problematize the home care proposed by the Melhor em Casa Program as a security tool/device, to understand the knowledge and the conditions of possibility that support its discursive network.…”
mentioning
confidence: 95%
“…Pårørende har mange roller og får ofte ansvaret for oppfølging av symptomlindring, komplekse omsorgsbehov, behandling og psykososial støtte (22). Pårørende blir derfor sentrale personer for å ivareta pasientens omfattende behov for omsorg og hjelp hjemme (22)(23)(24).…”
Section: )Pårørendes Perspektiv På Hjemmedødunclassified